Wpływ Wysokiego Komisarza OBWE do spraw Mniejszości Narodowych na ochronę praw mniejszości narodowych w państwach Azji Centralnej - Wojda, Rafał (Influence of the OSCE High Commissioner on National Minorities on the protection of the rights of national minorities in the countries of Central Asia)
In my dissertation, I refer to the human rights protection system created by the Organization for Security and Cooperation in Europe. It is the least known of the European human rights systems. The subject of the European Union, including its approach to the protection of human rights, is of great interest. There is a broadth of content on the Council of Europe, especially the European Court of Human Rights in Strasbourg. OSCE bodies do not enjoy such interest among scientists. One of the active organs of the OSCE is the High Commissioner on National Minorities. I am particularly interested in the specific form of activity of the High Commissioner by creating and promoting the so-called soft law. The recommendations of the High Commissioner refer to the norms of international law in the field of human rights protection. The originality of the selection of the topic lies in the fact that no scientific monograph on this topic has yet been prepared. There are no book publications in Polish literature that would comprehensively and thoroughly deal with the discussed topic. My doctoral dissertation was largely based on English-language literature (concerning the activities of the OSCE, and especially the High Commissioner on National Minorities) and Russian-language sources describing the legal and factual status of the implementation of the rights of national minorities in Central Asian countries.In my dissertation, I use general methodological methods of cognition. All the methods listed below are to verify the hypotheses. I follow the so-called the principle of the order of solving problems, which in an orderly manner allows to determine the legitimacy of the hypotheses. My dissertation meets the methodological requirement of considering phenomena in a specific way. I tried to take into account all the factors influencing the attitude of Central Asian states towards national minorities, such as legal, economic, historical, cultural, geopolitical and political. I used various perspectives: historical, systemic, structural, functional and prognostic. On the basis of the legal and dogmatic methods, an analysis of international law was made. This method was also used in the analysis of the national legislation of Central Asian states in the area of ​​protection of the rights of national minorities.